EU terrorism situation and trend report TE-SAT / EUROPOL / 2018 (EU terrorism situation and trend report TE-SAT, 2018)
This 2018 edition of the annual TE-SAT provides an overview of the nature and volume of terrorism that the EU faced in 2017. Although the majority of Member States reported that they did not experience any terrorist attacks during the reporting period, the human suffering and the threat of attacks remains high. In this report you will not only find information about how many terrorist attacks took place in 2017, but also the number of arrests and convictions for terrorist crimes. A brief overview of the terrorist situation outside the EU is also included.